ANALISIS KEAMANAN WEBSITE KOTA DEPOK MENGGUNAKAN METODE VULNERABILITY ASSESSMENT - Asep Kurniawan; Iik Muhamad Malik Matin (MULTINETICS, 2025)
The increasing use of the internet and websites also increases the threat level of hacking data and information on the internet, especially websites. The National Cyber and Crypto Agency (BSSN) noted that until April 2022, cyber attacks in Indonesia reached 100 million cases. The current rampant case is pishing using the .go.id domain. With the rise of these events to maintain and prevent intrusions and attacks, a security analysis of the website is carried out using the vulnerability assessment method using Owasp ZAP, Acunetix, Vega, Nessus and Skipfish tools that can help find out the vulnerabilities on the website. The purpose of this study is to obtain website vulnerabilities as an anticipatory step from intrusions and other attacks and to determine the level of vulnerability obtained so as not to become a threat to the website and an opportunity for hackers. The results of the analysis found that the depok.go.id website is not yet safe because there are still 5 types of vulnerabilities through internal and external networks with risk alert level High, namely: Hash Disclosure - Mac OSX salted SHA-1, DNS Server Spoofed request Amplification DDoS, Session Cookie Without Secure Flag, Integer Overflow, and Page Fingerprint Diffenrential Detected - Possible Local File Include.